UTILIZING NARRATIVE DESIGN IN E-COMMERCE CAMPAIGNS - Josimovski, Sasho; Pulevska ivanovska, Lidija; Kiselicki, Martin (International Scientific Conference Economic and Social Development, 2021)
The paper reseaches new and innovative methods for improving existing e-commerce and marketing strategies. As more businesses start their digital transformation during pandemic times, most efforts begin with the focus on marketing and e-commerce processes. This accelerated movement has created the opportunity to reach new potential consumers through new channels, so companies are focused on differentiating their offers on the market. Throughout the past years, there is extensive research on modeling an e-commerce and marketing strategy around product positioning (with the goal of giving the viewer context on how the product/service works and its intented benefits) versus modeling around narrative design (based around the creation of story-driven ads, placing the viewers in the middle and driving them through the sales funnel). The paper focuses on researching the effectiveness of product positioning, narrative design and interactive narrative design, as potential methods for the e-commerce landscape, through empirical research, secondary data and existing case studies on the topic. Data from the research shows that narrative design is dependent on a proper implementation to ensure its maximum potential, which can be followed as a model by companies.
Keywords: interactive narative design, product positioning, e-commerce, digital marketing transformation